Intellectual capital management and trust in public administration in European countries - Matos, F.; Valter Vairinhos; Matos, A. (Managing public trust, 2018)
This chapter presents an overview of the relationship between intellectual capital (IC) indicators and trust in public administration in European Countries. It intends to highlight empirical evidence that the countries with better indicators of trust are also those with better IC management and vice versa. In terms of originality, this chapter aims to contribute to the development of the practice and theory in this knowledge area, stimulating data-driven discussions about the factors that can explain trust and guide the formulation of policies and strategic planning. The way that countries deal with IC indicators is a decisive factor in their international reputations and in the success of a wide range of public policies that depend on behavioral responses from the public.